Assessing The Quality and Prioritize Improvements of E-government Using E-govqual and Importance Performance Analysis - Prasetyo, Beny; Adnan, Fahrobby; Darmawan, Jihan Tsanisya (Universitas Muhammadiyah Malang, 2023)
The Gresik Regency Government in 2020 has made new innovations in the development of E-Government as a form of implementing Presidential Regulation Number 3 of 2003 Regarding National Policy and Strategy for E-Government Development. Through the launch of the Pelayanan Online Pendaftaran Administrasi Kependudukan Gresik (Poedak) managed by the Population and Civil Registration Service. Poedak service aims to make it easier for the people of Gresik Regency to take care of population files. This study uses the E-GovQual method to measure the extent to which the quality of Poedak services is based on what users perceive, and the IPA method maps attributes according to improvement priorities. This study showed that the average score on the performance level assessment on all E-GovQual variables had a score of 3.13. Then the average score on the importance assessment on all E-GovQual variables was 3.08. So that the value of the gap between performance and importance can be known by 0.05. The results of the conformity analysis between the performance level and the importance level have a conformity value of >100% which is 102%. Thus, the overall performance of the Poedak service is good and meets the expectations or interests of users. There are 4 attributes that are included in quadrant 1, namely the quadrant with the main priority scale, namely an adequate response format (FIAA2), providing timely service (RA2), loading speed time on the website (RA5), and ease of understanding information content (CAIA6).